Increased functional connectivity strength of right inferior temporal gyrus in first-episode, drug-naive somatization disorder. (January 2015) - Su, Qinji; Yao, Dapeng; Jiang, Muliang; Liu, Feng; Jiang, Jiajing; Xu, Chunxing; Dai, Yi; Yu, Miaoyu; Long, Liling; Li, Hongzheng; Liu, Jianrong; Zhang, Zhikun; et al.
Background: Evidence of brain structural and functional alterations have been implicated in patients with somatization disorder (SD). However, little is known about brain functional connectivity in SD. In the present study, resting-state functional magnetic resonance imaging (fMRI) and graph theory were used to obtain a comprehensive view of whole-brain functional connectivity and to investigate the changes of voxel-wise functional networks in patients with SD. Methods: Twenty-five first-episode, medication-naive patients with SD and 28 age-, sex- and education-matched healthy controls (HCs) underwent resting-state fMRI. The graph theory approach was employed to analyze the data. Results: Compared to the HCs, patients with SD showed significantly increased functional connectivity strength in the right inferior temporal gyrus (ITG). There is a significant positive correlation between the z -values of the cluster in the right ITG and Hamilton Anxiety Scale scores. Conclusions: Our findings indicate that there is a disruption of the functional connectivity pattern in the right ITG in first-episode, treatment-naive patients with SD, which bears clinical significance.